(untitled) (CIPEEX, 2024)
THE AIM OF THIS STUDY IS TO DEVELOP A MINIMUM VIABLE PRODUCT (MVP) FOR A DIGITAL LOYALTY CARD TARGETED AT ULTRA COFFEE, A CAFETERIA FRANCHISE LOCATED ON THE CAMPUS OF THE UNIVERSIDADE EVANGÉLICA DE GOIS (UNIEVANGLICA). THE MOTIVATION FOR CREATING THIS PRODUCT AROSE AFTER OBSERVING THAT THE CURRENT PHYSICAL LOYALTY CARD FACES ISSUES SUCH AS LOSS AND FORGETFULNESS, WHICH IMPACTS THE ADHERENCE TO THE LOYALTY PROGRAM. THE METHODOLOGY APPLIED INVOLVED FIELD DATA COLLECTION WITH THE ANALYSIS OF 89 CUSTOMERS AND THEIR INTERACTIONS WITH THE PHYSICAL CARD. THE RESULTS SHOWED THAT 41.6% OF THE CUSTOMERS HAD THE PHYSICAL CARD, WHILE 58.4% DID NOT. AMONG THE CUSTOMERS WITHOUT A CARD, 9.6% HAD LOST IT, 34.6% HAD FORGOTTEN IT, AND 55.8% HAD NEVER RECEIVED ONE. ONLY 11.1% OF THE CUSTOMERS WHO FORGOT THEIR CARD RETURNED TO RETRIEVE IT. THIS INFORMATION HIGHLIGHTS THE NEED FOR A MORE EFFECTIVE AND ACCESSIBLE SOLUTION TO INCREASE ADHERENCE TO THE LOYALTY PROGRAM. THE PROPOSED MVP IS A DIGITAL LOYALTY CARD DEVELOPED TO ADDRESS THE CHALLENGES FACED WITH THE PHYSICAL CARD, SUCH AS LOSS AND FORGETFULNESS. THE DIGITAL PRODUCT WILL ENABLE CUSTOMERS TO ACCESS THE LOYALTY PROGRAM DIRECTLY ON THEIR MOBILE DEVICES, FACILITATING USAGE AND INCREASING ADHERENCE. THE IMPLEMENTATION OF THE DIGITAL LOYALTY CARD WILL ALSO BRING SIGNIFICANT BENEFITS TO ULTRA COFFEE. THE SOLUTION WILL ALLOW THE CAFETERIA TO OBTAIN VALUABLE INFORMATION ABOUT ITS CUSTOMERS, SUCH AS THE TOTAL NUMBER OF CUSTOMERS, THE AMOUNT OF ACCUMULATED POINTS, THE NUMBER OF CUSTOMERS WHO HAVE ALREADY RECEIVED LOYALTY REWARDS, AND A BETTER UNDERSTANDING OF THE CUSTOMER PROFILE. THIS DATA WILL HELP ULTRA COFFEE OPTIMIZE ITS OFFERINGS AND MARKETING STRATEGIES, THUS IMPROVING THE CUSTOMER EXPERIENCE AND RETENTION. DISCUSSIONS ABOUT THE PRODUCT ADDRESS THE POTENTIAL BENEFITS OF THE DIGITAL CARD FOR BOTH CUSTOMERS AND THE CAFETERIA, THE IMPORTANCE OF CATERING TO THE SPECIFIC NEEDS OF THE UNIVERSITY COMMUNITY, AND THE ABILITY TO COLLECT AND ANALYZE VALUABLE DATA TO IMPROVE ULTRA COFFEE€™S OPERATIONS. IN CONCLUSION, THE DEVELOPMENT OF A DIGITAL LOYALTY CARD HAS THE POTENTIAL TO SIGNIFICANTLY IMPROVE ADHERENCE TO ULTRA COFFEE€™S LOYALTY PROGRAM, INCREASING CUSTOMER SATISFACTION AND, POSSIBLY, RETENTION, AS WELL AS PROVIDING VALUABLE INSIGHTS FOR THE CAFETERIA€™S MANAGEMENT.